Photoreaction of Manganese Catalyst in Photosynthetic Oxygen Evolution - Cheniae, G. M. (1969)
The formation of active O(2) evolving centers following addition of Mn(2+) to Mn deficient Anacystis nidulans cells yielded an estimate of 6 to 12 Mn atoms associated with each O(2) evolving reaction center. Restoration of activity upon addition of Mn ions is affected in 3 ways: (1) Stimulation of the uptake of exogenous Mn into the cells—this uptake occurs in darkness, but is enhanced 5 to 10 fold by light; a high concentration of DCMU (1 × 10(−5)m) decreases this light enhanced influx no more than 50 to 75%; (2) Photoreactivation of the O(2) evolving centers, after excess Mn has been accumulated in the cells essentially no increase in Hill activity is observed unless the cells are illuminated. This photoreactivation is fully inhibited by 10(−6)m DCMU and partially by benzoquinone. The Q(10) of photoreactivation proper is close to 1; (3) Photoinhibition of the activation—photoreactivation occurs most effectively in weak intensities (< one-fiftieth photosynthetic saturation in normal cells). Apparently at higher intensities an inhibitory photoprocess is overriding. This inhibition proved reversible. The photoreactivation leads to new stable O(2) evolving centers as evidenced by an increase in the rate at saturating intensity, quantum yield, and the O(2) gush.